Does time spent using social media impact mental health?: An eight year longitudinal study. (March 2020) - Coyne, Sarah M.; Rogers, Adam A.; Zurcher, Jessica D.; Stockdale, Laura; Booth, McCall
Abstract: Many studies have found a link between time spent using social media and mental health issues, such as depression and anxiety. However, the existing research is plagued by cross-sectional research and lacks analytic techniques examining individual change over time. The current research involves an 8-year longitudinal study examining the association between time spent using social media and depression and anxiety at the intra-individual level. Participants included 500 adolescents who completed once-yearly questionnaires between the ages of 13 and 20. Results revealed that increased time spent on social media was not associated with increased mental health issues across development when examined at the individual level. Hopefully these results can move the field of research beyond its past focus on screen time. Highlights: Time spent using social media was not related to individual changes in depression or anxiety over 8 years. This lack of a relationship was found even in the transition between adolescence and emerging adulthood. Results were not stronger for girls or boys.